PENGARUH PRODUKSI, NILAI TUKAR DOLLAR AMERIKA SERIKAT, DAN INFLASI TERHADAP EKSPOR MINYAK SAWIT INDONESIA - Paramartha, I Putu Gde Deva Satria; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Indonesia is an agricultural and tropical country whose development is supported by the agriculture sub-sector. One of the agricultural sub-sectors is plantation. Plantation products are exported and become the leading commodity, namely palm oil. Palm Oil is one of Indonesia's main export commodities in international trade. The objectives of this study are (1) to analyze the effect of production, the US dollar exchange rate and simultaneous inflation on palm oil exports in Indonesia, and (2) analyze the effect of production, the US dollar exchange rate and partial inflation on palm oil exports in Indonesia. The data used is secondary data. The analysis technique used is multiple linear regression analysis. The results showed that Production, Dollar Exchange Rate, and inflation simultaneously affected Indonesian palm oil exports. Production has a positive and significant effect on Indonesia's palm oil exports. The US dollar exchange rate has a positive but not significant effect on Indonesia's palm oil exports. Inflation has a negative and not significant effect on Indonesia's palm oil exports. Keywords: Production, United States Dollar Exchange Rate, Inflation, Palm Oil Exports